Democracy, Economy, Progress and the Rule of Law. Special Reference to the Tax Regime for Religious Denominations - Catalá Rubio, Santiago (Journal of Finance and Financial Law, 2022)
The purpose of this article is twofold: on the one hand, to relate the fiscal and financial model to the Social and Democratic Rule of Law, on the other one, to transfer Spanish experiences that may be of interest to Poland, as both countries began their democratic experience and integration into the European Union a few decades ago. From a multidisciplinary perspective, the contributions that law could make to the field of political economy can be of capital importance for the consolidation of our democratic systems, public order, and social peace, analyzing the role of religious confessions. Methodology. To achieve this purpose, the analytical-comparative-interdisciplinary method was chosen as it was considered the most appropriate one in view of the close connections between economics, law, progress and social peace. The result of the research. The work shows that democracies, although they are the most effective models for achieving the highest standards of progress, and even though in the Polish and Spanish cases, they have the advantage of having served to bring dictatorial periods to an end, there is a need for effective control mechanisms. Democracies absolutely cannot degenerate into corrupt and ineffective systems under the control of large political and partisan oligarchies. The independence of the judiciary is, in this sense, an essential and inalienable element in guaranteeing the correct functioning of other state institutions. It is necessary to insist on the importance of the legal norm as an instrument of political control and its impact on macroeconomics, and the consolidation of democratic regimes, even more in the context initiated with the respective integration processes in the European Union. On the other hand, the aim is to show how beneficial tax treatment for religious denominations has a powerful effect on the achievement of the common good and social peace. In addition, it is about relating importance that has the budgetary balance and mechanisms for controlling public expenditure for the maintenance of progress and social justice in a sustainable model.